ASSESSMENT OF PREGNANCY AND DELIVERY MANAGEMENT IN WOMEN OF ADVANCED REPRODUCTIVE AGE - Gulammakhmudova Dilobar Valijanovna; Gulammakhmudova Odinabonu Abdusharof qizi (Modern American Journals, 2025)
The global rise in delayed childbearing has contributed to an increase in pregnancies among women of Advanced Maternal Age (AMA), typically defined as 35 years or older. While advancements in reproductive medicine have improved pregnancy outcomes, AMA continues to be associated with elevated maternal and neonatal risks. This systematic review aims to evaluate the impact of advanced maternal age on pregnancy and birth outcomes, synthesizing current evidence on associated complications such as preeclampsia, gestational diabetes, preterm birth, caesarean delivery, low birth weight, and neonatal intensive care requirements.
Keywords: Advanced Maternal Age (AMA), Pregnancy Outcomes, Preterm Birth, Gynaecology, Mother-Health, Gestational Diabetes, Preeclampsia, Caesarean Delivery, Low Birth Weight (LBW), Fatal Growth Restriction (FGR), Neonatal Intensive Care Unit (NICU), Assisted Reproductive Technology (ART), Maternal Health, Neonatal Outcomes, High-Risk Pregnancy, Delayed Childbearing, Maternal Age and Perinatal Risk.